2012
DOI: 10.1504/ijea.2012.049073
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure practices in Egypt: what are factors beyond the low level?

Abstract: In Egypt, as one of the emerging markets, mandatory disclosure of financial information on annual reports has attracted the attention of many researchers. Results of prior studies analysing disclosure level concluded that mandatory financial disclosure in annual reports is low. The purpose of this paper is to shed the light and analyse those factors affecting disclosure level in the Egyptian environment including political and economic conditions, legal system and regulatory framework, nature of the capital ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…However, our findings on voluntary disclosure level is supported by Ismail and Shehata (2012), who investigated the reporting environment in Egyptian context and concluded that the reasons behind the low level of disclosure are:…”
Section: Conclusion and Recommendations For Future Researchsupporting
confidence: 76%
“…However, our findings on voluntary disclosure level is supported by Ismail and Shehata (2012), who investigated the reporting environment in Egyptian context and concluded that the reasons behind the low level of disclosure are:…”
Section: Conclusion and Recommendations For Future Researchsupporting
confidence: 76%